1998
DOI: 10.1183/09031936.98.11051064
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic inflammation in cough variant asthma

Abstract: Eosinophils are considered to play a central pathogenetic role in asthma. We previously reported that sputum eosinophilia was observed in patients with cough variant asthma (CVA), as well as in "classic" asthma with wheezing. This study was undertaken to further investigate the involvement of eosinophils in CVA. The serum eosinophil cationic protein (ECP) level, the percentage of eosinophils in bronchoalveolar lavage (BAL) fluid, and the number of eosinophils in bronchial biopsy specimen were examined in 14 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
1
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(175 citation statements)
references
References 24 publications
6
160
1
8
Order By: Relevance
“…FUJIMURA et al [20] found high rates of sputum eosinophilia suggesting that their group of adults with chronic cough may have been asthmatic [20]. NIIMI et al [21] found that percentages of eosinophils and ECP in the cough group were similar to that of confirmed asthmatics and significantly higher than controls. MCGARVEY et al [22] using a comprehensive diagnostic protocol for chronic nonproductive cough in adults, divided patients according to aetiology of cough.…”
Section: Normalmentioning
confidence: 98%
“…FUJIMURA et al [20] found high rates of sputum eosinophilia suggesting that their group of adults with chronic cough may have been asthmatic [20]. NIIMI et al [21] found that percentages of eosinophils and ECP in the cough group were similar to that of confirmed asthmatics and significantly higher than controls. MCGARVEY et al [22] using a comprehensive diagnostic protocol for chronic nonproductive cough in adults, divided patients according to aetiology of cough.…”
Section: Normalmentioning
confidence: 98%
“…An elevated number of eosinophils and metachromatic cells are found in sputum samples of patients with asthma, CVA and EB [102,103]. Recognition of airway eosinophilic inflammation may assist in the assessment of the cause of chronic cough, as well as in the selection of treatment options.…”
Section: Sputum Analysismentioning
confidence: 99%
“…In the recent years there has been an increase in our understanding of the pathophysiology of cough-variant asthma, nonasthmatic eosinophilic bronchitis and atopic cough [Brightling et al 2003[Brightling et al , 2002[Brightling et al , 2000a[Brightling et al , 2000bBrightling and Pavord, 2000;Niimi et al 2000Niimi et al , 1998]. These three conditions have similar immunopathological characteristics with classic asthma in the form of an eosinophilic-driven inflammatory process.…”
Section: Pathophysiology Of Atypical Asthmamentioning
confidence: 99%
“…Whilst eosinophilic inflammation forms a common pathophysiological characteristic of classic asthma, cough-variant asthma, nonasthmatic eosinophilic bronchitis and atopic cough are distinct due to the differences in the location of the inflammatory cells and the thickness of the subepithelial layer reported in these conditions, hence the likely reasons for the phenotypical disparity observed [Brightling et al 2002;Niimi et al 1998]. …”
Section: Pathophysiology Of Atypical Asthmamentioning
confidence: 99%